Fatigue har en inverkan på fysisk aktivitet hos personer med Multipel Skleros - Clingston, My; Elofsson, Emelie (2013)
Introduction: Multiple Sclerosis (MS) is a chronic neurological disease that affects the central nervous system. Common symptoms are optic neuritis, muscle weakness in the extremities, fatigue, spasticity, balance impairment and pain. Fatigue is one of the most common symptoms and is believed to be experienced by 78 to 95 % of people afflicted with MS. Treatment for fatigue caused by MS can either be pharmacological or non-pharmacological. Recent studies have shown that different types of exercise can reduce fatigue. However, there are hardly any studies regarding fatigue and its impact on exercise. The aim of this study was to study if people with MS and fatigue believed that fatigue had an impact on their exercise. Methods: A total of 134 questionnaires were sent out to people with MS in the north (n=60) and the south (n=74) of Sweden. Questionnaires were distributed by Neurologiskt Handikappades Riksförbund and through a private practice in southern Sweden. The questionnaire consisted of the Fatigue Severity Scale and questions about fatigue and its impact on exercise. Results: 62 questionnaires were received out of 134, which gives an answering frequency of 46 % and 58 of the questionnaires were analyzed. 29 out of 35 in northern Sweden had fatigue and a majority of them believed that fatigue had an impact on their exercise. In southern Sweden 17 out of 23 had fatigue. A majority of them believed that fatigue had an impact on their exercise as well. Conclusion: Fatigue is a common symptom among people with MS. A majority considered that fatigue has an impact on their exercise and as a physiotherapist can this knowledge be useful to set up the structure for physical activity. Keywords: exercise, fatigue, Multiple Sclerosis, physiotherapy Validerat; 20130126 (global_studentproject_submitter)